SOLVING LINEAR PROGRAMMING PROBLEMS IN OPTIMIZATION OF ECONOMIC PROCESSES USING THE SIMPLEX METHOD (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2026)
This article describes the essence, algorithm, and practical application of the simplex method , one of the most effective and universal methods used to solve linear programming problems . In most cases, the problem of finding an optimal solution in linear programming problems cannot be solved using geometric methods, especially when the number of unknowns is more than three. Therefore, a special algorithmic approach is required to solve large-scale problems. The article presents the theoretical foundations of the simplex method, and explains in detail the process of transforming the problem into a canonical form, selecting an initial base solution, and achieving an optimal solution through successive iterations using an example. Obtained results of the simplex method efficiency and practical issues in solution convenience shows .​